International Perception of Competence, Education, and Training Needs Among Biomedical Professionals Involved in Medicines Development - Imamura, Kyoko; Criscuolo, Domenico; Jurczynska, Anna; Kesselring, Gustavo; Stonier, Peter; Tsuda, Tatsushi; Silva, Honorio (Frontiers in Pharmacology, 2019)
The development of new medicines requires today a multi-professional workforce both in the industry and the clinical research arena. Pharmaceutical physicians (PPs) and medicines development scientists (MDS) need a level of competencies which could be achieved by on-the-job experience, although must be completed through postgraduate education or continuous professional development programs. In order to assess the self-perception of competence, education and training needs, an on-line questionnaire based on the seven domains of competence developed by IFAPP-PharmaTrain was prepared and distributed among PPs and MDS members of IFAPP’s affiliated professional associations in countries with facilities for postgraduate education. The data collection was run over a fixed period of three months in Japan, Italy, Brazil and Spain during 2017. Results indicate low but variable levels of perceived competence for the various domains as well as seniority in the job. All respondents declared a significant need for continuing professional development in all domains. These results corroborate and support the continuous efforts, put in place by IFAPP and the PharmaTrain Federation, to foster the development of accredited education and training among professionals involved in medicines development.